Role of the histone deacetylase family in lipid metabolism: Structural specificity and functional diversity - Yunxia Li; Qi Han; Yuxin Liu; Jie Yin; Jie Ma (Pharmacological Research)
Lipids play crucial roles in signal transduction. Lipid metabolism is associated with several transcriptional regulators, including peroxisome proliferator activated receptor γ, sterol regulatory element-binding protein 1, and acetyl-CoA carboxylase. In recent years, increasing evidence has suggested that members of the histone deacetylase (HDAC) family play key roles in lipid metabolism. However, the mechanisms by which each member of this family regulates lipid metabolism remain unclear. This review discusses the latest research on the roles played by HDACs in fat metabolism. The role of HDACs in obesity, diabetes, and atherosclerosis has also been discussed. In addition, the interaction of HDACs with the gut microbiome and circadian rhythm has been reviewed, and the future development trend in HDACs has been predicted, which may potentiate therapeutic application of targeted HDACs in related metabolic diseases.